Neutrophil-and Endothelial Cell-Derived Extracellular Microvesicles Are Promising Putative Biomarkers for Breast Cancer Diagnosis. - Moreira, Thayse Batista (2025)
Fundação Oswaldo Cruz. Instituto Rene Rachou. Grupo Integrado de Pesquisas em Biomarcadores. Belo Horizonte, MG, Brasil.